Pelaksanaan Program Merdeka Belajar Kampus Merdeka dalam Meningkatkan Kualitas Pendidikan di Indonesia - Trianung, Teguh; Gumilang, Syifa Retno; Umair, Zahid; Adilah, Khadijah; Sawal, Muhamad Ramadan; Kosam, Fifty Ayu Lestari (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2024)
The existence of the Ministry of Education and Culture policy related to Merdeka Belajar Kampus Merdeka Program (MBKM) is the right effort in creating a generation that has soft skills and hard skills, and is qualified in aspects of leadership and personality. The MBKM program was launched in 2020 as a new breakthrough for the Ministry of Education and Culture to increase the flexibility of Indonesia's higher education system. MBKM provides greater autonomy for universities and students in designing study programs through student exchange schemes, partner internships, to research or field projects.MBKM is one of the policies of the Minister of Education and Culture, Nadiem Makariem. One of the programs of this MBKM policy is the Right to Study Three Semesters Outside the Study Program. The focus of this study is to analyze the implementation of MBKM comprehensively in improving the quality of education in Indonesia, so that it can be useful for formulating strategies for improvement and development of MBKM policies in the future. The research method used is a literature study of the material or research that has been done. From the results of the study, it can be seen that the implementation of MBKM helps students in their self-development, in addition, additional skills and student academic achievement also increase.